Psychologically supportive design guidelines for the wellbeing of healthcare staff: a study of primary healthcare premises in the UK - Ramadan, Amal (2020)
The rapid changing life pace and the increasing work challenges are ‎constantly raising the demands placed on employees. This flags the ‎importance of promoting employees’ health and wellbeing in their work ‎environments to deal with challenges that organisations currently face ‎towards building healthier workplaces that support the mental and physical ‎health of working staff.‎ National Health Service (NHS) is one of the top organisations facing increasing ‎challenges that affect staffs’ mental health and wellbeing. In addition to ‎budget shortage and financial challenges, staff may now be paying the cost of ‎an industrial design heritage, which values functionality and standardisation ‎over humanitarian philanthropic design. This is reflected in the status of ‎primary healthcare infrastructure, which is now providing mass NHS services ‎within an inefficient spatial environment and relatively poor workplace ‎quality.‎ Considering the important role that primary healthcare employees play in ‎contemporary life, and realising the challenges they face, this research ‎project develops a set of design recommendations that help with achieving a ‎psychologically supportive working environment for primary healthcare staff ‎in the UK. The research identifies fifteen psychologically supportive stimuli ‎‎[PSDS] that affect mental health and wellbeing of staff in primary healthcare ‎premises.‎ Adopting a realistic approach, this qualitative doctorate project employs ‎Evidence-Based Design, as a methodological guiding framework. The ‎research is composed of three main stages: The first phase is a primary ‎formulation of hypostatical theory, which delineates and evaluates the ‎primary potential environmental stimuli that affect users’ wellbeing, through ‎the inductive analysis of extensive multi-disciplinary literature review of three ‎main different disciplines, namely: psychology, medicine and architecture. ‎This is followed by two stages of two separate rounds of interviews. The ‎outcomes from the three stages are then contrasted for triangulation for ‎further data validation. The data validation process employs two methods: the ‎selective attention analysis and focus group (three focus groups were ‎conducted).‎ The research defines the associated stressors related to the current physical ‎work environment of primary healthcare in the UK and studies how staff ‎recognise, perceive and describe their physical working environment. The ‎research identifies fifteen PSDS: spatial layout, ergonomics, privacy, furniture, ‎safety & infection control, nature, views, light, colours, artwork, finishing ‎materials & textures, noises & sounds, shapes & patterns, natural ventilation ‎& thermal comfort, and water. The concluded stimuli are categorised under ‎two groups: functional and sensorial. Based on the analysis of the interviews, ‎these stimuli are re-defined and explained from two schematic perspectives: ‎the healing environment schemas and working environment schemas. ‎ Finally, this research argues that good healthcare services cannot be ‎managed without considering healthcare professionals’ wellness; factors such ‎as job stress and fatigue are directly related to their physical environment, ‎which may negatively affect both the staff’s physical and psychological ‎wellbeing, consequently affecting the quality of healthcare service delivery. ‎The research outcomes help decision-makers, designers, architects and ‎developers to better understand and consider the needs of primary ‎healthcare providers and guide the development of healthier primary care ‎environments to support the staff wellbeing within their workplace.‎